Bumblebees can be used in combination with juvenile hormone analogues and ecdysone agonists - Mommaerts, Veerle (Ecotoxicology (London, England), 2006)
This study examined the lethal and sublethal effects on the beneficial insect Bombus terrestris by two classes of insect growth regulators (IGRs) that are commercially used in agriculture to control pest insects. Three juvenile hormones analogues (JHAs) (pyriproxyfen, fenoxycarb and kinoprene) and two ecdysone agonists or moulting accelerating compounds (MACs) (tebufenozide and methoxyfenozide) were tested. The bumblebee workers were exposed to the insecticides via three different routes of exposure: dermally by topical contact, and orally via the drinking sugar water or the pollen. In the first series of experiments the IGRs were applied at their respective maximum field recommended concentration (MFRC). These risk hazard tests showed that the tested IGRs caused no acute toxicity on the workers, and any compound had an adverse effect on reproduction (production of males). In addition, larval development was followed in the treated nests compared with the controls. After application of the two MACs and the JHA fenoxycarb no adverse effects were observed on larval development. However, in the nests where the workers were exposed to the JHAs pyriproxyfen and kinoprene higher numbers of dead larvae were scored. These larvae were third and fourth instars, implying a lethal blockage of development before metamorphosis. In a second test, a series of dilutions was made for kinoprene, and these results revealed that only the MFRC caused a toxic effect on the larval development. On the other hand, kinoprene at lower concentrations (0.0650 mg ai/l) had a stimulatory effect on brood production. It was remarkable that ovaries of such treated dominant workers were longer and contained more eggs than in the controls. In a last experiment, the cuticular uptake was determined for a JHA and MAC to evaluate to what extent worker bees accumulate these classes of IGRs. Cuticular uptake ranged from 34 to 83% at 24 h after topical application. Overall, the obtained results indicate that the tested IGRs at their recommended concentration are safe to be used in combination with B. terrestris